Situation Report: Hungary, 17 May 1978 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Central Committee Assesses the Country's Situation Study Published on Factory Workers' Morale Life in a Socialist Society: Results of an Opinion Poll Housing: A Central Question of Social Policy Agricultural Study Tours to Western Countries Arouse Criticism Western Machinery: A Driving Force in Hungarian Agriculture Austria and Hungary Decide on Mutual Abolition of Visas